RAD52 S346X variant reduces breast cancer risk in BRCA2 mutation carriers. Issue 6 (21st April 2020) - Biswas, Kajal; Sharan, Shyam K.
Abstract : Adamson et al . report that BRCA2 mutation carriers inheriting RAD52 S346X variant have reduced breast cancer risk. The RAD52 S346X variant lacks the nuclear localization sequence, which mislocalizes the protein to the cytoplasm and renders it nonfunctional. Combined loss of BRCA2‐mediated DNA repair by homologous recombination and RAD52‐mediated single‐strand annealing may result in cell death and reduce breast cancer risk. Comment on: https://doi.org/10.1002/1878-0261.12665